Interpretation of the Psalm Genre in the Works of Jaroslav Zatloukal and Eugen Suchon - ROSUL, Tetiana (Studia Universitatis Babes-Bolyai Musica, 2024)
The article defines the originality of the concept and genre metamorphoses of the psalm on the example of "The Subcarpathian Psalm" by J. Zatloukal and the cantata "The Psalm of the Subcarpathian Land" by E. Suchon. The artists chose the psalm as an example of a universal genre, radically updating its canons in both figurative and formal aspects, which corresponds to the artistic trends of the XX century. Their works demonstrate a secular model of the genre, which is characterized by filling the poetic structure of psalmody with a specific historical meaning. The comparison of two works allows considering the specifics of the interpretation of spiritual, ethical and historical aspects in art in the unity of their content and form. It has been determined that the dialogic form of the poetic text, its appealing character and sublime oratorical tone correspond to the specifics of the psalm genre. In E. Suchon's interpretation, we can observe the stylistic emancipation of the musical language from the canons of any church or romantic fascination with folklore.